Surveillance of Mycoplasma agassizii in Texas tortoises (Gopherus berlandieri) for translocation with emphasis on treatment and recovery - Moeller, Christin A.; Perales, Saren; Rodriguez, Wraith; Martin, Alynn M.; Eversole, Cord B.; Rideout-Hanzak, Sandra; Crump, Paul; Hilton, Clayton D.; Henke, Scott E. (Frontiers in Veterinary Science, 2025)
BackgroundTexas tortoises (Gopherus berlandieri) are a Texas-state threatened species. Translocation is often suggested as a mitigation option; however, disease status and the potential for spread must be considered prior to such efforts. Mycoplasma infection of the upper respiratory tract is a concern within tortoise populations, which requires monitoring so translocation efforts do not inadvertently spread the disease.ObjectivesWe determined and compared the prevalences of Mycoplasma agassizii in Texas tortoises from donor and recipient sites in southern Texas prior to translocation, treated Mycoplasma agassizii-infected tortoises with danofloxacin, and developed alternate Mycoplasma agassizii treatments for Texas tortoises.MethodsWe collected 171 and 23 Texas tortoises from a 270-ha and a 100-ha donor site and recipient site, respectively. We began a regimen of danofloxacin (6 mg/kg body weight injected subcutaneously every other day for 30 days) for tortoises with clinical signs (N = 20). We noted an additional 10 tortoises began displaying clinical signs of upper respiratory tract disease (URTD) after translocation, so we designed a trial to test tulathromycin (5 mg/kg body weight given intramuscularly once/week for 7 weeks) or oxytetracycline (8 mg/kg body weight given subcutaneously once/day for 14 days) as Mycoplasma treatments for symptomatic tortoises.ResultsWithin the donor and recipient sites, 56 (32.7%) and 8 (34.8%), respectively, had antibody titers suggestive of past exposure. Eighteen tortoises from the donor site (10.5%) and 2 from the recipient site (8.7%) displayed clinical signs (i.e., clear serous nasal discharge, conjunctivitis, and palpebral edema) consistent with Mycoplasmal URTD upon initial collection, even though all polymerase chain reaction (PCR) results were negative for active shedding of Mycoplasma agassizii. We ceased treatment after the first dose of danofloxacin due to adverse reactions, which only began to subside after 72 h from the initial dose. Neither tulathromycin or oxytetracycline caused the clinical signs of URTD to subside after a 50-day treatment period.ConclusionMycoplasma is a persistent issue facing Texas tortoises. Stressors, such as translocation, can cause Mycoplasma-seropositive tortoises to display clinical symptoms of URTD, which can abate without treatment, once the stressor subsides.ImplicationsDanofloxacin, the recommended treatment for Mycoplasma infection in tortoises, is too potent for Texas tortoises.